A Mixed Length Scale Model for Migrating Fluvial Bedforms. Issue 15 (3rd August 2020) - Guala, M.; Heisel, M.; Singh, A.; Musa, M.; Buscombe, D.; Grams, P.
Abstract: With the expansion of hydropower, in‐stream converters, flood‐protection infrastructures, and growing concerns on deltas fragile ecosystems, there is a pressing need to evaluate and monitor bedform sediment mass flux. It is critical to estimate real‐time bedform size and migration velocity and provide a theoretical framework to convert easily accessible time histories of bed elevations into spatially evolving patterns. We collected spatiotemporally resolved bathymetries from laboratory flumes and the Colorado River in statistically steady, homogeneous, subcritical flow conditions. Wave number and frequency spectra of bed elevations show compelling evidence of scale‐dependent velocity for the hierarchy of migrating bedforms observed in the laboratory and field. New scaling laws were applied to describe the full range of migration velocities as function of two dimensionless groups based on the bed shear velocity, sediment diameter, and water depth. Further simplification resulted in a mixed length scale model estimating scale‐dependent migration velocities, without requiring bedform classification or identification. Plain Language Summary: Sand and gravel sediment in river beds often forms wave‐like patterns called ripples or dunes, which are collectively referred to as bedforms. The flow of the river causes bedforms to form and slowly travel downstream, thus contributing to sediment transport, erosion, and deposition along the river and to the evolution of deltas. Predicting how fast bedforms move can improve our ability to estimate sediment load carried by rivers. In this study, experimental measurements of bedforms in a laboratory facility and in the Colorado River are used to better understand bedform movement. This study confirms that smaller bedforms move faster than larger bedforms and provides a simple equation to predict the speed of moving bedforms of different sizes based on the bedform length, the size of the sediment grains, and the depth of the river. Key Points: Scale‐dependent bedform migration velocities are confirmed using laboratory and field measurements Bedform velocity depends on stream depth, sediment diameter and shear velocity, reorganized into frictional and bankfull scaling parameters A mixed length scale is proposed in a simplified predictive model